Human α defensins promote the expression of the inflammatory cytokine interleukin‐8 under high‐glucose conditions: Novel insights into the poor healing of diabetic foot ulcers. Issue 8 (3rd June 2019) - Meng, Lanxia; Guo, Xingchen; Yang, Xilin; Liu, Hongyue; Yu, Mosheng; Wu, Yingliang; Zhu, Zhanyong
Abstract: Sustained infection and chronic inflammation are the most common features and complex mechanisms of diabetic foot disease. In this study, we examined the expression and functional roles of human endogenous α defensins in diabetic foot ulcer. The expression levels of human α defensins HNP1, HNP3, and HNP4 were significantly higher in the wound center than the edge of diabetic foot ulcers. And the inflammatory cytokine interleukin IL‐8 (IL‐8) was also highly expressed in wound exudates. In human foreskin fibroblasts, these human α defensins were found only slightly to affect IL‐8 expression directly. hemoglobin A1C (HbA1c) is the main clinical indicator of diabetic foot disease. Advanced glycation end products of bovine serum albumin (AGE‐BSA), as HbA1c analogue, was found to promote IL‐8 expression. Human α defensins, in the presence of AGE‐BSA, further significantly promoted IL‐8 expression. These findings showed that human α defensins aggravated the inflammatory response in diabetic foot ulcers patients, providing new insights in to the poor healing of diabetic foot ulcers.